Language and the Complex of Ideology A Socio-Cognitive Study of Warfare Discourse in Britain - Douifi, Mohamed (Cham : Springer International Publishing, 2018)
This book undertakes a systematic analysis of the workings of ideology in discourse, using an interdisciplinary approach that links language, cognition and society. Through examination of two corpora - a collection of British newspaper articles and a set of political speeches - the author examines Britain's involvement in the Iraq War (2003), and critically assesses the language practices which constructed a pro-war ideology under Tony Blair's premiership. Drawing on a constellation of concepts from van Dijk's socio-cognitive model, this book carries out both qualitative and quantitative analyses and conceptualises discourse as a nonlinear, highly discursive and socio-cognitive phenomenon. This innovative work will appeal to students and scholars of Cognitive Linguistics, Quantitative Linguistics, Social Constructivism, Critical Discourse Analysis, Political Sciences and Communication Studies.
Chapter 1: Introduction -- Chapter 2: Basic Theoretical Insights on Ideology and Discourse Analysis -- Chapter 3: Contemporary Orientations in Discourse Studies -- Chapter 4: The Anglo-Iraqi Relationships: A historical overview -- Chapter 5: Blair's Foreign Policy Discourse on Iraq -- Chapter 6: The Discursive Construction of the Iraq War in the British 'Quality' Press -- Chapter 7: Conclusion.
Social Sciences
text file PDF
Keywords: Discourse analysis; Corpora (Linguistics).; Communication; Great Britain-Politics and government; Cognitive grammar; Cognitive psychology